KUALITAS KIMIA DAGING SAPI BALI YANG DIMARINASI DALAM EKSTRAK DAUN KELOR, TEH DAUN KELOR, DAN BUBUK DAUN KELOR - I. M. P., GUNAWAN; SRIYANI, N. L. P.; WIBAWA, A. A. P. P. (Fakultas Peternakan Universitas Udayana, 2023)
Moringa oleifera leaves contain antioxidant compounds that play a role in preventing lipid oxidation in beef. This study aimed to find out the best product and comprehend the chemical quality of the result of marinated bali beef with moringa oleifera leaves extract, moringa oleifera leaves tea, and moringa oleifera leaves powder. Ma- rinating in this study was conducted for 1 hour at cold temperatures. The research design used was a completely randomized design with 4 treatments and 4 replications. The four treatments were meat that was not marinated (P0), 0,4% of moringa leaves extract marinated meat (P1), 0,4% of moringa leaves tea marinated meat (P2), 0,4% of moringa leaves powder marinated meat (P3). The variables observed were moisture, ash, protein, fat and carbohy- drate. The results indicated that the marinated bali beef in moringa leaves extract, moringa leaves tea, and moringa leaves powder had a significant effect (P<0,05) on protein content which tended to increase and the fat content decreases, but had no significant effect (P>0,05) on moisture, ash, and carbohydrate contents. From the results of this study, it can be concluded that for marinating bali beef, the best used is moringa oleifera leaves powder filtrate of 0,4% which can increase the protein content and decrease the fat content of bali beef.